Analiza antropologiczna szkieletów ze Stręgoborzyc, woj. małopolskie - Mietlińska, Joanna (Acta Universitatis Lodziensis. Folia Archaeologica, 2017)
This thesis is an anthropological analysis of an early-medieval population, inhabiting the area of Stręgoborzyce village, Igołomia-Wawrzeńczye commune, Małopolska province. The subjects of research were skeletons of 67 individuals, which were dug during archaeological excavations on site number 38 in Stręgoborzyce, in years 2010 and 2011. Among the 67 skeletons of different state of preservation there were isolated 22 females, 17 males, 4 children and 24 individuals of unknown sex. Basic research included determining the age and sex of the individuals and the state of preservation of skeletal remains. Author did some cranial and postextracranial skeleton measurements, which allowed doing an anthropological characterization of the population and estimating a hypothetical intravital body length of each individual. The evaluation of health conditions was taken on the basis of pathological changes in bone material, which are an expression of previous diseases and degenerative processes. The thesis also focused on the examination of the presence of non-metric characteristics of the human skeleton. At the end author tried to do a comparison analysis of the population to other groups, similar in time and geography.